Gender-Based Perceptions of Postgraduate Defense Sessions and Seminar Feedback at the University of Zambia - A Quantitative Perspective - Kenneth Kapalu Muzata (CV. Samuel Manurung and Co, 2026)
This quantitative study investigates postgraduate students’ perceptions of feedback received during seminar presentations and defense sessions at the University of Zambia. Drawing on a self-selection sample of 75 master's and doctoral candidates across various faculties, the research examined the quality, tone, and impact of feedback on students’ academic development. Quantitative analysis revealed generally high levels of satisfaction with feedback across key research components, including proposal writing, literature review, methodology, and data analysis. Notably, feedback on methodology approached statistical significance as a concern, and perceptions of external examiners varied significantly by gender. While lecturers and examiners were identified as the most helpful sources of feedback, lecturers were also cited as the most frequent source of demeaning comments, highlighting a tension between authority and emotional safety in academic critique. Anchored in a social constructivist framework, the study emphasizes the relational nature of feedback and its role in shaping academic identity. The findings underscore the need for more empathetic, structured, and inclusive feedback practices to enhance postgraduate research quality and student well-being